Diagnoza wybranych elementów kompetencji gramatycznej maturzystów w wypowiedzi pisemnej - Gierzyńska, Marta (Acta Neophilologica, 2023)
It is no secret that productive skills, regardless of the educational stage, present the most challenges to the learners of a foreign language. The practical use of specific structures in speech or writing is closely associated with the act of communication. The following article aims to analyze mistakes in the use of verbs based on written statements in the German language in the basic-level high school leaving exam. The research material consists of papers from high school graduates in the Warmia and Mazury and Podlaskie Voivodeships in the 2022/2023 school year. The low results achieved by graduates in the correct use of grammatical elements within written statements should encourage teachers and examiners to reflect on the reasons for this situation, especially considering similar results in the national report, which includes data from other regions. The empirical part of this article is preceded by a theoretical discussion related to the definition of grammar, its significance in foreign language education, as well as its place among other language skills, considering the communicative and task-based approach. The articles conclusion provides a description of strategies and techniques for effective development of grammar competence. The discourse takes on a research and review character.